Private property, freedom and power - Salgado Muñoz, Constanza (The University of Edinburgh, 2020)
This thesis aims to shed light on a central aspect of private property: the limits that it imposes on the freedom of non-owners and its potential implications. To the extent that private property does not depend on the physical connection between the owner and the object, accumulation becomes normatively possible because one can be an owner of more things that one can physically hold or protect from others. The situation that private property enables is not only that people may have no opportunity to acquire and be an owner, but more importantly, that it may leave people without the possibility of satisfying their needs by using objects that otherwise would be available for everyone’s use. In the first part of the thesis, I examine three different justifications for private property produced within the liberal/libertarian canon. I will use these accounts to investigate what follows for a justification of private property from considering its passive side of the property relation. The general idea is that a justification of private property demands consideration of the interests of nonowners: of their unfreedom and its potential implications regarding the justification of a private property system. In the second part of the thesis, I intend to demonstrate that private property not only gives freedom to owners but also may give them power. There is certainly a sense in which private property always gives power to owners. Private property gives to owners the power to pursue aims that otherwise would be either impossible or very difficult to achieve. However, great unequal distributions of private property may give to owners not only power to, but also power over people. Given the fact that accumulation may leave individual needs unmet, private property becomes an important power resource. The second part of the thesis is dedicated to show that in its capitalist articulation, private property gives a dominating power to owners in two main spheres: the economic and the political spheres. This task turns to be more difficult than it might superficially appear to be, as political philosophy does not provide an adequate general framework for thinking about private domination.
Keywords: property; freedom; power; domination; limits of freedom; private property; unfreedom